Comparative Genome Analysis Provides Insights into Both the Lifestyle of Acidithiobacillus ferrivorans Strain CF27 and the Chimeric Nature of the Iron-Oxidizing Acidithiobacilli Genomes - Tran, Tam T. T.; Mangenot, Sophie; Magdelenat, Ghislaine; Payen, Emilie; Rouy, Zoé; Belahbib, Hassiba; Grail, Barry M.; Johnson, D. Barrie; Bonnefoy, Violaine; Talla, Emmanuel (Frontiers in Microbiology, 2017)
The iron-oxidizing species Acidithiobacillus ferrivorans is one of few acidophiles able to oxidize ferrous iron and reduced inorganic sulfur compounds at low temperatures (<10ºC). To complete the genome of At. ferrivorans strain CF27, new sequences were generated, and an update assembly and functional annotation were undertaken, followed by a comparative analysis with other Acidithiobacillus species whose genomes are publically available. The At. ferrivorans CF27 genome comprises a 3,409,655 bp chromosome and a 46,453 bp plasmid. Not surprisingly, At. ferrivorans CF27 possesses genes allowing its adaptation to cold, metal(loid)-rich environments, as well as others that enable it to sense environmental changes, allowing At. ferrivorans CF27 to escape hostile conditions and to move towards favourable locations. Interestingly, the genome of At. ferrivorans CF27 exhibits a large number of genomic islands (mostly containing genes of unknown function), suggesting that a large number of genes has been acquired by horizontal gene transfer over time. Furthermore, several genes specific to At. ferrivorans CF27 have been identified that could be responsible for the phenotypic differences of this strain compared to other Acidithiobacillus species. Most genes located inside At. ferrivorans CF27-specific gene clusters which have been analysed were expressed by both ferrous iron-grown and sulfur-attached cells, indicating that they are not pseudogenes and may play a role in both situations. Analysis of the taxonomic composition of genomes of the Acidithiobacillia infers that they are chimeric in nature, supporting the premise that they belong to a particular taxonomic class, distinct to other proteobacterial subgroups.